PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP PENINGKATAN HASIL BELAJAR ANAK PEKERJA MIGRAN DI SANGGAR BIMBINGAN SENTUL, MALAYSIA - Nur Kholifah; Iwan Kuswandi; Yeni Puji Astuti (LPPM IAD Probolinggo, 2024)
This research was motivated by the condition of migrant workers' children in phase C at the Sentul Guidance Center, Malaysia. In Learning, children tend to be passive and only listen to the educator's explanations. Meanwhile, the learning models, methods and media used are still centered on educators. This is a factor causing the low learning outcomes of migrant workers' children in Malaysia. The purpose of this study is to find out how much the influence of the example non examples learning model on the learning outcomes of migrant worker children at the Sentul Guidance Center, Malaysia. This research is a pre-experimental one group pretest posttest research. The data collection technique in this study is the Saturated Sample Technique. The data analysis techniques used in this study are analysis requirements tests and hypothesis tests with t-tests. The average value of the pretest was 40.00 and the average score of the posttest was 82.00, an increase of 42.00. The alternative hypothesis test criteria (H1) was accepted while the null hypothesis (H0) was rejected based on the t-test findings, which showed a Sig (2-tailed) value of 0.000 < 0.05. Keywords: Model example non example ; Learning Outcomes; Children of migrant workers